Development of community participation process of partners group involved with community security along border in Sisaket Province to decrease an inequity by community-based - Saeanphuwa, Emon (Journal of Social Development and Management Strategy, 2021)
The findings of this research found that the context of the developing partners group of community security migrated to live at Ban Kantrom Tai about 80 years. In 1973, there was an idea awareness in struggling between classes until 1976. The government used dictatorship to cruelly arrest and detain the people. This incident was called "Communist Party of Thailand" The villagers had already been alerted, so they fought with the government. In 1980, the government launched 66/2523 policy to stop fighting and develop the nation. In addition, the government named the group "The Group of developing partners of Thailand" conforming to 66/2523 in the period of General Prem Tinsulanonda as a Prime Minister. Regarding the problems, they were divided into 4 aspects: farmlands, debt, low price of agricultural products and unemployment. On the needs aspect, they consisted of insurance of higher price of rubber and rice, water system management and youth training. Furthermore, the development guidelines were training on jobs and debt reduction methods, grouping agriculturists to sell agricultural products, farming for living and sale, providing farmlands, providing welfare of cost price products, promoting suitable crop rotation, promoting love in the family and encouraging youth to continue higher education. Finally, the three concepts of community participation process and six aspects on processes to develop community participation consisted of knowledge, jobs, equality creation, communication, grouping based on needs and providing community as a base for development.